Laminate
By stacking the base coat layer of styrene-based material on the surface of the copper foil, and combining the intermediate layer and the polyimide adhesive layer, the problem of difficult to take into account both the adhesiveness and electrical characteristics of the copper foil in the prior art is solved, and a laminate with high adhesiveness, good electrical characteristics and heat resistance is achieved.
Patent Information
- Application Number
- CN202380059926.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to take into account the adhesion and electrical properties of copper foils, and also has heat resistance.
A copper foil with a surface Rz of 1.2 μm or less was used, and a base coat layer was laminated on the surface, and the base coat layer contained 30 to 90% by mass of a styrene-based elastomer or a styrene-group-containing silane coupling agent. The laminate further includes an intermediate layer and an adhesive layer, which contains a polyphenylene-based oligomer having reactive terminal groups, and the adhesive layer is an adhesive layer for polyimide.
It realizes high adhesion and good electrical characteristics of copper foil, and has heat resistance, which is suitable for the transmission of high-frequency signals.
Smart Images

Figure CN119731022A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated body. Background Art
[0002] A flexible copper clad laminate (hereinafter referred to as "FCCL") for transmission of high-frequency signals is manufactured using a resin copper foil having a resin layer laminated on one side of the copper foil (for example, see paragraph
[0105] of Patent Document 1). In addition, paragraph
[0123] of Patent Document 1 states that the polyimide layer laminated between the metal layer and the adhesive layer is a three-layer structure having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer.
[0003] Patent Document 1: Japanese Patent Application Publication No. 2021-160148 Summary of the invention
[0004] Compounds with polar functional groups are preferred to improve the adhesion to copper foil, but polar functional groups tend to increase the dielectric constant of the resin. In addition, it is preferred to roughen the surface of the copper foil to improve the adhesion between the copper foil and the resin, but the roughening of the copper foil tends to increase the transmission loss of the signal path formed by the copper foil. Therefore, it is difficult to achieve both adhesion to the copper foil and electrical properties.
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a laminate that can achieve a balance between adhesion to copper foil and electrical properties and heat resistance.
[0006] In order to solve the above-mentioned problems, the present invention provides a laminate comprising a copper foil having a surface Rz of 1.2 μm or less and a primer layer laminated on the surface of the copper foil, wherein the primer layer is formed to contain a styrene-based elastomer having a styrene content of 30 to 90% by mass or a styrene-containing silane coupling agent.
[0007] The laminate is preferably formed by laminating an intermediate layer and an adhesive layer in this order on the primer layer.
[0008] The adhesive layer is preferably an adhesive layer for polyimide for bonding the laminate to a polyimide resin.
[0009] The adhesive layer for polyimide preferably contains less than 50% by mass of a resin having a glass transition temperature (Tg) of 50° C. or lower, and is cured by heating with a thermal radical initiator.
[0010] The intermediate layer preferably contains a polyphenylene oligomer having a reactive terminal group and is formed by heat curing with a thermal radical initiator.
[0011] The present invention also provides a laminated body comprising a polyimide resin layer and a laminated body formed by laminating the polyimide resin layer on both sides of the polyimide resin layer via the adhesive layer for polyimide.
[0012] According to the present invention, it is possible to provide a laminate that can achieve a balance between adhesiveness to copper foil and electrical properties and heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a cross-sectional view showing an example of the laminated body according to the first embodiment.
[0014] Figure 2 This is a cross-sectional view showing an example of a laminated body according to the second embodiment.
[0015] Figure 3 This is a microscope photograph showing a part of the cross section of the laminate of Example 1 in an enlarged manner. DETAILED DESCRIPTION
[0016] Hereinafter, the present invention will be described based on preferred examples.
[0017] Figure 1 An example of the laminated body 10 according to the first embodiment is shown. Figure 2 An example of the laminated body 20 of the second embodiment is shown. These drawings are schematically shown, and the shapes, sizes, scales, details of fine parts, etc. of each part may be different from the actual shapes, etc. The up-down direction of the drawings is the thickness direction of the laminated body 10, 20. The left-right direction of the drawings can be any direction as long as it is orthogonal to the thickness direction of the laminated body 10, 20, and can be the length direction of the laminated body 10, 20 or the width direction.
[0018] The laminate 10 of the first embodiment includes a copper foil 11 and a primer layer 12 laminated on a surface 11a of the copper foil 11. The surfaces 11a and 11b of the copper foil 11 have an Rz of 1.2 μm or less. The primer layer 12 contains a compound having a group derived from styrene.
[0019] The copper foil 11 is not particularly limited, and examples thereof include rolled copper foil, electrolytic copper foil, oxygen-free copper foil, tough copper foil, etc. The copper foil 11 is a flexible conductor layer and is excellent in electrical conductivity, thermal conductivity, and the like.
[0020] The surfaces 11a and 11b of the copper foil 11 are two surfaces in the thickness direction of the copper foil 11. The surfaces other than the surfaces 11a and 11b of the copper foil 11 may be cut surfaces, etc., and therefore may not necessarily be in the same state as the surfaces 11a and 11b. The thickness of the copper foil 11 is not particularly limited, but is preferably thin from the viewpoint of suppressing the total thickness of the FCCL, and for example, 5 to 35 μm can be cited.
[0021] In the laminate 10 of the first embodiment, the Rz of the surfaces 11a and 11b of the copper foil 11 is 1.2 μm or less. The Rz of both the surfaces 11a and 11b of the copper foil 11 may be 1.2 μm or less. When the primer layer 12 is laminated on one side of the copper foil 11, it is preferred that the Rz of the surface 11a on at least one side where the primer layer 12 is laminated is 1.2 μm or less.
[0022] Here, the surface roughness Rz of the copper foil 11 is a ten-point average roughness measured based on JIS B 0601-1994. This corresponds to RzJIS in JIS B 0601-2001 and later (corresponding to ISO 42871997).
[0023] The surfaces 11a and 11b of the copper foil 11 may be low-roughened surfaces or non-roughened surfaces. The non-roughened surfaces are any surfaces that are not roughened, and Rz is not limited to zero. The surfaces 11a and 11b with low Rz may be smoothed surfaces.
[0024] Specific examples of Rz are not particularly limited as long as they are within the above range, and may be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm or 1.2 μm, or values near or in between these ranges.
[0025] The primer layer 12 is laminated on at least one of the surfaces 11 a and 11 b of the copper foil 11 with respect to the resin layer laminated thereon in order to improve the adhesiveness with the copper foil 11 .
[0026] The laminate 10 may also have a structure in which a plurality of resin layers including a primer layer 12 are laminated on a copper foil 11 as a resin copper foil. Although not particularly illustrated, it may also have a double-layer structure in which only the primer layer 12 is laminated on one side of the copper foil 11. When manufactured with a double-layer structure, another resin layer may be laminated on the primer layer 12 in a subsequent process.
[0027] The primer layer 12 is preferably laminated on at least the surface 11a of the copper foil 11 on which the adhesive layer 14 is laminated via the intermediate layer 13. Although not particularly shown, the primer layer 12 may be laminated on both surfaces of the copper foil 11.
[0028] The thickness of the primer layer 12 is not particularly limited, but is preferably 0.1 to 3 μm, more preferably 0.2 to 2 μm, and further preferably 0.5 to 1.5 μm.
[0029] The primer layer 12 is a layer containing at least one resin or organic compound as a primer. The primer layer 12 contains a compound having a group derived from styrene as at least one of the resin or organic compound. In addition, the primer layer 12 may contain other components such as a surface modifier as long as the adhesiveness and heat resistance are not impaired.
[0030] The compound containing a group derived from styrene is not particularly limited as long as it can be used as a primer, and examples thereof include styrene-based elastomers, styrene-containing silane coupling agents, etc. The compound containing a group derived from styrene may be a solid substance or a liquid substance at a room temperature of 20 to 25°C.
[0031] From the viewpoint of achieving both adhesion to the copper foil 11 and electrical properties and heat resistance, in the laminate 10 of the first embodiment, the primer layer 12 is formed to contain a styrene-based elastomer having a styrene content of 30 to 90% by mass or a silane coupling agent containing a styrene group. As a first embodiment, the primer layer 12 may be formed to contain a styrene-based elastomer having a styrene content of 30 to 90% by mass. As a second embodiment, the primer layer 12 may be formed to contain a silane coupling agent containing a styrene group.
[0032] The styrene-based elastomers include copolymers based on block structures and / or random structures of conjugated diene compounds and aromatic vinyl compounds (hereinafter referred to as "conjugated diene-aromatic vinyl copolymers") and hydrogenated products thereof. In addition, copolymers based on block structures and / or random structures of aliphatic olefins and aromatic vinyl compounds (hereinafter referred to as "aliphatic olefin-aromatic vinyl copolymers") can be mentioned.
[0033] Examples of the conjugated diene compound include butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene.
[0034] Examples of the aromatic vinyl compound include styrene, tert-butylstyrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylstyrene, N,N-diethyl-p-aminoethylstyrene, vinyltoluene, and 4-tert-butylstyrene.
[0035] Examples of the aliphatic olefins include ethylene and units derived from α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, vinylcyclohexane and / or cyclic olefins, i.e., units of α-olefin monomers and cyclic olefin monomers such as cyclopentene and norbornene.
[0036] As specific examples of the conjugated diene-aromatic vinyl copolymer and its hydride, styrene-ethylene copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isoprene-butadiene-styrene block copolymer (SIBS), styrene-ethylene-butylene-olefin crystalline block copolymer (SEBC), hydrogenated styrene-butadiene rubber (HSBR), etc. can be cited. In addition, these copolymers can also be modified conjugated diene-aromatic vinyl copolymers modified with unsaturated carboxylic acids. The conjugated diene-aromatic vinyl copolymer and its hydride can also be unmodified styrene elastomers that are not modified with polar functional groups such as carboxylic acid groups.
[0037] The conjugated diene-aromatic vinyl copolymer and its hydride can be modified by using polar functional groups such as carboxylic acid groups. The modification method is not particularly limited, and can be graft modification such as melt-kneading a monomer containing a polar functional group with a polyolefin resin in the presence of a free radical polymerization initiator such as an organic peroxide or an aliphatic azo compound, or copolymerization with a monomer containing a polar functional group.
[0038] Examples of the monomer containing a polar functional group include compounds having an olefinic double bond such as a vinyl group and a polar functional group such as a carboxylic acid group in the molecule. Specific examples include various unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, unsaturated dicarboxylic anhydrides, etc. The styrene-based elastomer may contain one monomer containing a polar functional group, or two or more monomers may be used in combination.
[0039] Examples of the unsaturated monocarboxylic acid include acrylic acid and methacrylic acid.
[0040] Examples of the unsaturated dicarboxylic acid include α,β-unsaturated carboxylic acids such as maleic acid, nadic acid, fumaric acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, tetrahydrophthalic acid, and endo-bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic acid (Endic acid).
[0041] Examples of the unsaturated dicarboxylic anhydride include maleic anhydride, nadic anhydride, itaconic anhydride, citraconic anhydride, and endo-nadic anhydride.
[0042] At least a portion of the polar functional group-containing monomer may be maleic anhydride.
[0043] As specific examples of the aliphatic olefin-aromatic vinyl copolymer, for example, a method of polymerizing an α-olefin and an aromatic vinyl compound using a compound having a plurality of transition metals and a plurality of cyclopentadienyl skeletons and an organic aluminum oxide compound or an organic boron as a catalyst is known (for example, Japanese Patent Publication No. 10-168112, Japanese Patent Publication No. 2001-354724, International Publication No. 01 / 68719), etc. In addition, a styrene-ethylene copolymer described in Journal of the American Chemical Society, 2004, Vol. 126, No. 43, pages 13910 to 13911 is also known.
[0044] The styrene elastomer may be used alone or in combination of two or more copolymers. From the viewpoint of adhesion and electrical properties, the styrene content in the styrene elastomer is preferably 30 to 90% by mass, more preferably 40 to 80% by mass, and further preferably 50 to 70% by mass.
[0045] The styryl-containing silane coupling agent is a compound having a styryl group and an alkoxysilyl group in the molecule. Examples of the styryl group include o-styryl, m-styryl, p-styryl, methylstyryl, and chlorostyryl.
[0046] Examples of the alkoxysilyl group include a trimethoxysilyl group, a triethoxysilyl group, a methyldimethoxysilyl group, and a methyldiethoxysilyl group.
[0047] Specific examples of the styryl group-containing silane coupling agent include p-styryltrimethoxysilane and p-styryltriethoxysilane.
[0048] The material may be applied to thinly form the primer layer 12. The coating apparatus for the primer layer 12 is not particularly limited, and examples thereof include a gravure coater, a knife coater, a reverse coater, a rod coater, a spray coater, a spin coater, a die coater, a slit coater, a roll coater, and a dip coater.
[0049] In order to improve the bonding strength between the copper foil and the resin, it is preferred to increase the Rz of the copper foil, but it is known that this will affect the high-frequency transmission characteristics. However, it is believed that in the laminate 10 of the present invention, even if the Rz of the copper foil 11 is small, the primer layer 12 is well bonded to the surface 11a of the copper foil 11, so the bonding strength is improved.
[0050] The laminate 10 is formed by laminating an adhesive layer 14 on the surface of the primer layer 12 opposite to the copper foil 11 via an intermediate layer 13. The laminate 10 of the illustrated example includes the copper foil 11, the primer layer 12, the intermediate layer 13, and the adhesive layer 14 in this order.
[0051] The intermediate layer 13 is an arbitrary layer laminated between the primer layer 12 and the adhesive layer 14. The intermediate layer 13 may be a single layer or may include two or more layers. The intermediate layer 13 may include a resin layer having heat resistance and low dielectric constant properties.
[0052] The intermediate layer 13 preferably contains a polyphenylene oligomer having a reactive terminal group and is cured by heat with a thermal free radical initiator. The intermediate layer 13 may be formed only of the polyphenylene oligomer and a thermosetting resin layer containing the thermal free radical initiator, or may be formed to include the thermosetting resin layer and other layers.
[0053] The polyphenylene oligomer used for the intermediate layer 13 is an oligomer having a phenylene group as a repeating unit. The polyphenylene oligomer is not particularly limited, and examples thereof include oligomers such as polyphenylene ether (PPE), polyphenylene sulfide (PPS), and polyphenylene sulfone (PPSU).
[0054] The phenylene group contained as a repeating unit of the polyphenylene-based oligomer may be an unsubstituted phenylene group or a substituted phenylene group such as dimethylphenylene. Examples of the substituent of the substituted phenylene group include alkyl groups such as methyl groups, aryl groups such as phenyl groups, and halogen atoms such as chloro groups.
[0055] The polyphenylene oligomer is a polymer having a lower degree of polymerization than a polyphenylene polymer, and oligophenylene ether (OPE) is preferred. The number average molecular weight of the polyphenylene oligomer is, for example, 500 to 5,000.
[0056] The reactive terminal group of the polyphenylene oligomer is preferably a thermosetting functional group that is cured by heating with a thermal radical initiator. The thermosetting functional group is not particularly limited, and examples thereof include vinyl, allyl, styryl, acryloyl, methacryloyl, and epoxy groups.
[0057] The thermal radical initiator used in the intermediate layer 13 is not particularly limited, and examples thereof include organic peroxides, aliphatic azo compounds, etc. The organic peroxide may be a compound having an aromatic group, an aliphatic group, or an alicyclic group. The proportion of the thermal radical initiator is not particularly limited, and may be 0.1 to 5% by mass.
[0058] The thermosetting resin layer of the intermediate layer 13 may contain one or more selected from polymers other than polyphenylene oligomers, monomers, fillers, and the like.
[0059] The polymer that can be used for the thermosetting resin layer is not particularly limited, and examples thereof include bismaleimide resins.
[0060] The monomer that can be used for the thermosetting resin layer is not particularly limited, and examples thereof include styrene-based monomers such as styrene, methylstyrene, and tert-butylstyrene.
[0061] The filler that can be used in the thermosetting resin layer is not particularly limited, and examples thereof include inorganic oxides such as silica and alumina. The filler preferably has a particle size smaller than the layer thickness. The filler may be spherical or true spherical.
[0062] The thickness of the intermediate layer 13 is not particularly limited, but is preferably 1 to 10 μm, more preferably 3 to 8 μm, and even more preferably 4 to 7 μm.
[0063] The adhesive layer 14 is a layer for bonding the laminate 10 to other resin layers, and may be a single layer or may include two or more layers. The adhesive layer 14 may also be a polyimide adhesive layer for bonding to a polyimide resin. The adhesive layer 14 has a peel strength of, for example, 0.5 N / mm or more relative to the polyimide resin. These polyimide adhesive layers may be bonded to the polyimide resin layer 15 of the laminate 20 of the second embodiment described later, or may be bonded to other polyimide resins. For example, the laminate 10 may be laminated only on one side of the polyimide resin layer 15 via the adhesive layer 14.
[0064] The polyimide adhesive layer preferably contains less than 50% by mass of a resin having a glass transition temperature (Tg) of 50°C or less and is cured by heating with a thermal radical initiator. The polyimide adhesive layer may contain 50% by mass or more of a resin having a Tg of more than 50°C.
[0065] The resin used for the adhesive layer 14 is not particularly limited, and examples thereof include oligophenylene ether (OPE), bismaleimide resin, etc. For example, oligophenylene ether (OPE) is a resin having a Tg of more than 50°C, and bismaleimide resin is a resin having a Tg of 50°C or less.
[0066] The Tg of the resin having a Tg higher than 50° C. may be, for example, 100 to 250° C. The ratio of the Tg of the resin having a Tg higher than 50° C. may be, for example, 60 to 90% by mass.
[0067] The Tg of the resin having a Tg of 50° C. or less may be, for example, 30 to 50° C. The ratio of the Tg of the resin having a Tg of 50° C. or less may be, for example, 10 to 40% by mass.
[0068] The thermal radical initiator used in the adhesive layer 14 is not particularly limited, and examples thereof include organic peroxides and aliphatic azo compounds. The organic peroxide may be a compound having an aromatic group, an aliphatic group, or an alicyclic group. The proportion of the thermal radical initiator is not particularly limited, and may be 0.1 to 5% by mass.
[0069] The thickness of the adhesive layer 14 is not particularly limited, but is preferably 0.1 to 3 μm, more preferably 0.2 to 2 μm, and further preferably 0.5 to 1.5 μm.
[0070] When oligophenylene ether (OPE) is used for the intermediate layer 13 and the adhesive layer 14, the same OPE may be used or different OPEs may be used. When thermal radical initiators are used for the intermediate layer 13 and the adhesive layer 14, the same thermal radical initiators may be used or different thermal radical initiators may be used.
[0071] In order to form the intermediate layer 13 and the adhesive layer 14 thinly, a material such as a resin may be applied. The coating apparatus is not particularly limited, and examples thereof include a gravure coater, a knife coater, a reverse coater, a bar coater, a spray coater, a spin coater, a die coater, a slit coater, a roll coater, and a dip coater.
[0072] When applying the materials of the primer layer 12, the intermediate layer 13, and the adhesive layer 14, the physical properties such as concentration and viscosity can be adjusted by using an organic solvent appropriately according to the respective materials. The organic solvent is not particularly limited, and examples thereof include aromatic solvents such as toluene and xylene; ether solvents such as diethyl ether and tetrahydrofuran; ketone solvents such as acetone and methyl ethyl ketone; ester solvents such as ethyl acetate and γ-butyrolactam; amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; sulfur solvents such as dimethyl sulfoxide and tetramethylene sulfone, etc. The organic solvent may be a mixed solvent containing two or more solvents.
[0073] Figure 2 The laminate 20 shown has a structure in which the laminate 10 is laminated on both sides of the polyimide resin layer 15 via the adhesive layer 14. That is, the copper foil 11 is laminated on both sides of the thickness direction of the laminate 20, and the polyimide resin layer 15 is arranged in the center of the laminate 20. The copper foil 11 and the polyimide resin layer 15 are bonded together by an adhesive structure including at least three layers of the primer layer 12 / intermediate layer 13 / adhesive layer 14. As described above, the primer layer 12 is laminated on the surface of the copper foil 11, and the adhesive layer 14 is an adhesive layer for polyimide bonded to the polyimide resin layer 15.
[0074] The laminated bodies 10 and 20 can be used for manufacturing high-frequency circuits. The polyimide resin layer 15 preferably contains a polyimide resin having heat resistance and low dielectric constant characteristics, and the polyimide resin may be a modified polyimide (MPI) resin.
[0075] The modified polyimide resin is not particularly limited, and examples thereof include amino-modified polyimide resins, isocyanate-modified polyimide resins, urethane-modified polyimide resins, silicone-modified polyimide resins, siloxane-modified polyimide resins, and terminal-modified polyimide resins.
[0076] In the laminated bodies 10 and 20 , it is preferred that at least the adhesive layer 14 contains a thermosetting adhesive, and the intermediate layer 13 may also contain a thermosetting adhesive.
[0077] The manufacturing method of the laminate 20 is not particularly limited, and the laminate 10 having at least four layers of copper foil 11 / primer layer 12 / intermediate layer 13 / adhesive layer 14 can be bonded to both sides of the polyimide resin layer 15. Alternatively, a laminate 21 having at least three layers of copper foil 11 / primer layer 12 / intermediate layer 13 can be bonded to both sides of a laminate 22 having adhesive layers 14 laminated on both sides of the polyimide resin layer 15.
[0078] There is no particular limitation on the lamination method of the stack 20, and there are heat pressing and hot lamination. Conditions such as temperature, pressure, and time can be appropriately set and changed. When the treatment is divided into two or more stages, the temperature, pressure, etc. can also be different in each stage.
[0079] The hot press can be performed by sandwiching the stacked laminate 10 , the polyimide resin layer 15 , and the laminate 10 with stainless steel plates, and heating at 100 to 200° C. and 3 MPa for 2 hours.
[0080] Thermal lamination is a method of laminating the stacked laminate 10, the polyimide resin layer 15, and the laminate 10 at 100 to 180°C and 0.7 MPa, and then thermally curing by post-curing. The post-curing conditions can be, for example, 100 to 180°C and 2 hours.
[0081] When the resin layer shrinks while being attached to the surface of the copper foil, there may be defects such as a gap between the copper foil and the resin layer, and the bonding strength may be reduced. Even in the laminate 10, 20, when the intermediate layer 13 and / or the adhesive layer 14 are heated and cured, these layers may shrink. However, it is believed that since the primer layer 12 is well bonded to the surface 11a of the copper foil 11 in the laminate 10, 20, even if the intermediate layer 13 and / or the adhesive layer 14 shrinks during curing, the reduction in bonding strength can be suppressed.
[0082] The use of the laminates 10 and 20 is not particularly limited, and for example, materials for flexible printed circuits (FPC) for high-frequency transmission, flexible copper clad laminates (FCCL), etc. can be cited. As a method of forming a circuit from the copper foil 11, etching processing using photolithography can be cited. The copper clad laminate (CCL) using the laminates 10 and 20 can be a single-sided copper clad laminate or a double-sided copper clad laminate.
[0083] As mentioned above, although this invention was demonstrated based on the preferred embodiment, this invention is not limited to the said embodiment, Various changes are possible within the range which does not deviate from the summary of this invention.
[0084] Example
[0085] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not particularly limited to these.
[0086] [Preparation Example 1 of Thermosetting Varnish]
[0087] In a pressure-resistant container with stirring wings equipped with a cooler and a vacuum line on the upper part of the container, 56 parts by mass of polyphenylene ether resin (trade name: OPE-2St 2,200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 28 parts by mass of bismaleimide resin (trade name: SLK-3000, manufactured by Shin-Etsu Chemical Co., Ltd.), and 26 parts by mass of tert-butyl styrene (reagent manufactured by Tokyo Chemical Industry Co., Ltd.) were added and stirred. The mixture was concentrated under reduced pressure for 18 hours at -0.07 MPa and a jacket temperature of 30°C to remove the toluene solvent. Then, 16 parts by mass of methyl ethyl ketone (reagent manufactured by Tokyo Chemical Industry Co., Ltd.), 140 parts by mass of silica slurry (trade name: SC2050-MTX, manufactured by Admatechs Co., Ltd.), and 4.8 parts by mass of a curing agent (trade name: PERHEXA (registered trademark) V, manufactured by NOF Corporation) were added and stirred until homogeneous to prepare a varnish of methyl ethyl ketone solvent. The solid content was calculated and found to be 76% by mass.
[0088] [Preparation Example 2 of Thermosetting Varnish]
[0089] A varnish of methyl ethyl ketone solvent was prepared in the same manner as in Production Example 1 except that the bismaleimide resin in Production Example 1 was changed to 32 parts by mass of bismaleimide resin (trade name: SLK-2700, manufactured by Shin-Etsu Chemical Co., Ltd.) The solid content was calculated to be 75% by mass.
[0090] [Preparation Example 3 of Thermosetting Varnish]
[0091] In a pressure-resistant container equipped with a stirring blade and equipped with a cooler and a vacuum line on the upper part of the container, 118 parts by mass of a polyphenylene ether resin (trade name: OPE-2St 2,200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 24 parts by mass of a bismaleimide resin (trade name: SLK-1500, manufactured by Shin-Etsu Chemical Co., Ltd.), and 2.0 parts by mass of a curing agent (trade name: Parahexar (registered trademark) V, manufactured by NOF Corporation) were added and stirred until homogeneous to prepare a varnish of a methyl ethyl ketone solvent. The solid content was calculated and found to be 71% by mass.
[0092] The components shown in Table 1 are as follows.
[0093] <Styrene elastomer>
[0094] (A)-1: "TUFTEC (registered trademark) H1043" (manufactured by Asahi Kasei Corporation, styrene-ethylene-butylene-styrene block copolymer, styrene content 67% by mass)
[0095] (A)-2: "TUFTEC (registered trademark) H1517" (manufactured by Asahi Kasei Corporation, styrene-ethylene-butylene-styrene block copolymer, styrene content 43% by mass)
[0096] (A)-3: "TUFTEC (registered trademark) H1052" (manufactured by Asahi Kasei Corporation, styrene-ethylene-butylene-styrene block copolymer, styrene content 20% by mass)
[0097] (A)-4: "SEPTON (registered trademark) 2104" (manufactured by Kuraray Co., Ltd., styrene-ethylene-propylene-styrene block copolymer, styrene content 65% by mass)
[0098] (A)-5: "HYBRAR (registered trademark) 7125F" (manufactured by Kuraray Co., Ltd., styrene-ethylene-propylene-styrene block copolymer, styrene content 20% by mass)
[0099] <Acid-modified styrene elastomer>
[0100] (B)-1: "TUFTEC (registered trademark) M1911" (manufactured by Asahi Kasei Corporation, modified styrene-ethylene-butylene-styrene block copolymer, styrene content 30% by mass)
[0101] (B)-2: "TUFTEC (registered trademark) M1943" (manufactured by Asahi Kasei Corporation, modified styrene-ethylene-butylene-styrene block copolymer, styrene content 20% by mass)
[0102] <Styrene polymer>
[0103] (C)-1: "SGP10" (manufactured by PS Japan Co., Ltd., polystyrene)
[0104] (C)-2: "G9001" (manufactured by PS Japan Co., Ltd., styrene-(meth)acrylic acid copolymer)
[0105] (C)-3: "MS600" (manufactured by TOYO STYRENE CO., LTD., styrene-methyl methacrylate copolymer)
[0106] (C)-4: "MS-NIP" (manufactured by Denka Co., Ltd., styrene-maleic anhydride-N-phenylmaleimide copolymer)
[0107] <Styrene group-containing silane coupling agent>
[0108] ·(D)-1: "KBM-1403" (manufactured by Shin-Etsu Chemical Co., Ltd., p-styryltrimethoxysilane)
[0109] <Thermosetting varnish>
[0110] (E)-1: Production Example 1
[0111] (E)-2: Production Example 2
[0112] (F)-1: Production Example 3
[0113] [Example 1]
[0114] On an electrolytic copper foil (trade name: CF-T9DA-SV-12, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., thickness: 12 μm, Rz: 0.85 μm) as a copper foil, a 10% by mass toluene solution of a styrene-based elastomer (A)-1 was uniformly applied to a thickness of about 1 μm after drying, and then heated and dried at 110°C for 5 minutes, and then the solvent was removed. Next, a thermosetting varnish (E)-1 was uniformly applied thereon to a thickness of about 6 μm after drying, and then heated and dried at 80°C for 5 minutes, and then the solvent was removed to prepare a single-sided copper-clad laminate having a primer layer and an intermediate layer.
[0115] Next, a toluene solution of thermosetting varnish (F)-1 was uniformly applied to one side of a polyimide film (Kapton (registered trademark) 150LK, manufactured by DU PONT-TORAY CO., LTD.) so that the thickness after drying was about 1 μm, and then the solution was dried at 110° C. for 5 minutes, and then the solvent was removed. Next, a toluene solution of thermosetting varnish (F)-1 was uniformly applied to the surface on the opposite side of the polyimide film so that the thickness after drying was about 1 μm, and then the solution was dried at 110° C. for 5 minutes, and then the solvent was removed to prepare a polyimide film with adhesive layers for polyimide on both sides.
[0116] Two single-sided copper-clad laminates and a polyimide film with adhesive layers for polyimide on both sides are prepared, and after being stacked in the order of single-sided copper-clad laminate / polyimide film with adhesive layers for polyimide on both sides / single-sided copper-clad laminate, they are heat-pressed at 150°C and 3.0 MPa for 30 minutes and then heat-pressed at 180°C and 3.0 MPa for 60 minutes to produce a double-sided copper-clad laminate.
[0117] [Examples 2 to 6, Comparative Examples 1 to 9]
[0118] With the compositions shown in Table 1, double-sided copper-clad laminates of Examples 2 to 6 and Comparative Examples 1 to 9 were produced in the same manner as in Example 1.
[0119] <Adhesion Test>
[0120] For the double-sided copper-clad laminate, the peel strength (N / mm) was measured according to JIS C 6481 (Testing methods for copper-clad laminates for flexible printed circuit boards). The 90° peel strength was preferably 0.5 N / mm or more, more preferably 0.6 N / mm or more. The results are shown in Table 1.
[0121] <Welding heat resistance test>
[0122] The double-sided copper-clad laminate was placed in a thermostatic chamber at 23°C and 50% humidity for 24 hours, then placed in a solder bath at 288°C, and the time until deformation and blistering occurred was measured to evaluate heat resistance. The results are shown in Table 1.
[0123] [Table 1]
[0124]
[0125] As shown in Table 1, the peel strength of Examples 1 to 6, which have a primer layer formed of a styrene-based elastomer or a styrene-containing silane coupling agent containing 30 to 90% by mass of styrene, is 0.5 N / mm or more. In addition, Examples 1 to 6 also have excellent welding heat resistance. On the other hand, the peel strength of Comparative Examples 1 to 3, which have a primer layer formed of a styrene-based elastomer containing less than 30% by mass of styrene, is 0.4 N / mm or less, which is not sufficient. In addition, the peel strength and welding heat resistance of Comparative Examples 4 to 7 using styrene-based polymers are not sufficient.
[0126] Figure 3 This is a photograph obtained by cutting a cross section of the laminate (double-sided copper-clad laminate) produced in Example 1 and photographing a portion of the cross section using an electron microscope. "um" in the photograph means μm.
[0127] The bright layer shown at the bottom of the photo is copper foil 11. The layer indicated as "1.15um" on it is primer layer 12. The layer indicated as "5.40um" on it is intermediate layer 13. The layer indicated as "992nm" on it is adhesive layer 14. The uppermost part on it is polyimide film (polyimide resin layer) 15. "7.46um" indicates the range of the adhesive structure including primer layer 12 / intermediate layer 13 / adhesive layer 14. The white spheres are silica particles (fillers).
[0128] Description of Reference Numerals
[0129] 10, 20, 21, 22: laminate, 11: copper foil, 11a, 11b: surface, 12: primer layer, 13: intermediate layer, 14: adhesive layer, 15: polyimide resin layer
Claims
1. A laminate comprising a copper foil having a surface Rz of 1.2 μm or less and a primer layer laminated on the surface of the copper foil, The primer layer is formed to contain a styrene-based elastomer having a styrene content of 30% to 90% by mass or a styrene group-containing silane coupling agent.
2. The laminate according to claim 1, wherein The laminate is formed by laminating an intermediate layer and an adhesive layer in this order on the primer layer.
3. The laminate according to claim 2, wherein: The adhesive layer is an adhesive layer for polyimide for bonding the laminate to a polyimide resin.
4. The laminate according to claim 3, wherein: The adhesive layer for polyimide contains less than 50% by mass of a resin having a glass transition temperature of 50° C. or lower, and is cured by heating with a thermal radical initiator.
5. The laminate according to claim 3 or 4, wherein The intermediate layer contains a polyphenylene oligomer having a reactive terminal group and is cured by heating with a thermal radical initiator. 6 . A laminated body, wherein the laminated body according to claim 3 is laminated on both surfaces of a polyimide resin layer via the adhesive layer for polyimide.
Citation Information
Patent Citations
Catalyst for copolymerization of alpha-olefin and aromatic vinyl compound, production of copolymer of alpha-olefin and aromatic vinyl compound, and new transition metal compound
JP1998168112A
Alpha-olefin / Aromatic vinyl compound copolymer
JP2001354724A
Resin film, metal-clad laminate and circuit board
JP2021160148A
Transition metal catalyst component for polymerization and process for producing polymer with the same
WO2001068719A1
Felting laminate for resin and method for manufacturing laminated body using same
CN101157837A